Analiza prometnih nezgod zaradi nepravilne smeri na cestah z omejenim dostopom - Krivec, David (Zdravstveno varstvo, 2004)
The purpose of the study was to determine the number of traffic accidents occurring on Slovene motorways as a result of wrong-way driving, and to definecharacteristics common to these accidents. The study included traffic accidents documented during the period 1998-2002. The basic source of information was the Slovene traffic accident database. Statistical analysis was done to determine characteristics of traffic accidents and traffic accidents causers, and to identify differences in traffic accident distribution between accidents caused by wrong-way driving and accidents due to other causes. Accidents as a result of driving the wrong way are mainly dueto misperception of traffic signals. These accidents are characterized by more severe injuries than other types of accidents. As indicated by the GIS-based analysis, used to identify the highest accident density locations on the road network, the highest accident density was observed in the intersection areas.
Keywords: analiza; ceste; nepravilna smer vožnje; prometne nezgode; vzroki